2012
DOI: 10.1371/journal.pone.0038837
|View full text |Cite
|
Sign up to set email alerts
|

Parkin Promotes Degradation of the Mitochondrial Pro-Apoptotic ARTS Protein

Abstract: Parkinson’s disease (PD) is associated with excessive cell death causing selective loss of dopaminergic neurons. Dysfunction of the Ubiquitin Proteasome System (UPS) is associated with the pathophysiology of PD. Mutations in Parkin which impair its E3-ligase activity play a major role in the pathogenesis of inherited PD. ARTS (Sept4_i2) is a mitochondrial protein, which initiates caspase activation upstream of cytochrome c release in the mitochondrial apoptotic pathway. Here we show that Parkin serves as an E3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 91 publications
(134 reference statements)
1
24
0
Order By: Relevance
“…Parkin expression has been reported to protect cells against multiple forms of stress [42] , but although the exact mechanism of this prosurvival function remains elusive, accumulating evidence exists that it involves inhibition of programmed cell death (apoptosis). Two recent studies identified Bax and the mitochondrial pro-apoptotic protein ARTS as Parkin substrates that both might contribute to the anti-apoptotic effect of Parkin [43] , [44] . In our study, we identified novel associations between Parkin and several proteins involved in cell death processes.…”
Section: Discussionmentioning
confidence: 99%
“…Parkin expression has been reported to protect cells against multiple forms of stress [42] , but although the exact mechanism of this prosurvival function remains elusive, accumulating evidence exists that it involves inhibition of programmed cell death (apoptosis). Two recent studies identified Bax and the mitochondrial pro-apoptotic protein ARTS as Parkin substrates that both might contribute to the anti-apoptotic effect of Parkin [43] , [44] . In our study, we identified novel associations between Parkin and several proteins involved in cell death processes.…”
Section: Discussionmentioning
confidence: 99%
“…) and apoptosis‐related protein in the TGF‐beta signaling pathway (Kemeny et al . ; Bendikov‐Bar et al . ), which is deleterious to DA neurons (Imai et al .…”
Section: Molecular Link Between β‐Glucocerebrosidase Activity Presenmentioning
confidence: 99%
“…This is proposed to correlate with disease severity, since it was found to be most extensive for the L444P mutant, which is associated with GD type III in homozygosity (Bendikov-Bar et al 2011). A direct link between mutated GC induced ERAD and PD is provided by only one study demonstrating that expression of mutant L444P impairs parkin (Park2)-mediated ERAD of unfolded proteins (Ron et al 2010) interfering with the proteasomal degradation of parkin substrates such as parkin interacting substrate (Shin et al 2011;Bendikov-Bar et al 2014;Stevens et al 2015) and apoptosis-related protein in the TGF-beta signaling pathway (Kemeny et al 2012;Bendikov-Bar et al 2014), which is deleterious to DA neurons (Imai et al 2000;Shimura et al 2000;Ron et al 2010). How mutated GC affects ERAD and a-SN degradation remains elusive and clearly requires further experimental evidence and exploration.…”
Section: The Unexpected Link Between Gaucher and Parkinson's Diseasementioning
confidence: 99%
“…Overexpression of AIMP2 in the mouse at levels seen in PD leads to an age‐dependent degeneration of dopaminergic neurons and impairment of motoric skills. Other parkin substrates are PARIS (PARis Interacting Substrate) [Shin et al., ] and ARTS (apoptosis‐related protein in TGF beta signaling pathway, a spliced variant of SEPT4 , [NM_080415.3, NP_536340.1]) [Kemeny et al., ]. PARIS is a cytoplasmic protein whose degradation is regulated by parkin‐mediated ubiquitination.…”
Section: Cellular Dysfunction In Gaucher Diseasementioning
confidence: 99%